Does trade openness increase firm-level volatility? - Harald Strotmann; Jörg Döpke; Claudia M. Buch (Deutsche Bundesbank, 2006)
From a theoretical point of view, greater trade openness affects firm-level volatility by changing the exposure and the reaction of firms to macroeconomic shocks. The net effect is ambiguous, though. This paper provides firm-level evidence on the link between openness and volatility. Using two novel datasets on German firms, we analyze the evolution of firm-level output volatility and the link between volatility and trade openness. We find that firm-level output volatility displays patterns similar to those found in aggregated data for Germany. Also, smaller firms and firms that grow faster are more volatile. Increased trade openness tends to lower volatility.
Keywords: F41; E32; G15; 330; firm-level volatility; trade openness; Politik der offenen Tür; Außenhandelsliberalisierung; Wirtschaftspolitische Wirkungsanalyse; Produktion; Absatz; Volatilität; Schätzung; Deutschland